IMPLEMENTASI MANAJEMEN KURIKULUM PENDIDIKAN DI MADRASAH IBTIDAIYAH AL HUDA KARANGNONGKO - Yudha Indrayanto; Sayid Alwan Hadzami; Naila Aniqotun Ni'mah; Abdurrahman Abdurrahman (Hijri, 2025)
Implementation of the Independent Curriculum in the 2024/2025 Academic Year. MI Al-Huda, a madrasah, has implemented the independent curriculum in stages. This curriculum begins with training, technical guidance, or workshops for teachers so that they have sufficient understanding of the independent curriculum. Teachers at MI Al-Huda are also given the opportunity to be creative and adapt the curriculum to the conditions at school. The obstacles faced in implementing the independent curriculum are requiring teachers to learn differentially and limited facilities and infrastructure. MI Al-Huda hopes to improve Pancasila values through the development of the Pancasila profile. For example, the election of class leaders is carried out with the principles of devotion to Allah and democracy. Thus, MI Al-Huda strives to implement the independent curriculum effectively and in accordance with the conditions at school, as well as improve the quality of education through the creativity of teachers and the assistance of the development team.